2020
DOI: 10.1016/j.ebiom.2020.102979
|View full text |Cite
|
Sign up to set email alerts
|

Personalized four-category staging for predicting prognosis in patients with small bowel Adenocarcinoma: an international development and validation study

Abstract: Background Log odds of positive lymph nodes (LODDS) classification showed superiority over 8 th edition N staging in predicting survival of small bowel adenocarcinoma (SBA) patients. The aim of this study was to develop and validate the Tumor, LODDS, and Metastasis (TLM) staging of SBA. Methods Totally 1789 SBA patients from the Surveillance, Epidemiology, and End Results (SEER) database between 1988–2010, 437 patients from SEER database betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The only proven significant independent prognostic factor in the three cohorts was LODDS. LODDS is a newly identified promising index for prognosis prediction, which has been verified in several malignancies, such as small bowel adenocarcinoma [ 18 , 19 ], gastric cancer [ 20 ], and AEG [ 12 , 21 ]. With data from the SEER database, Xu et al [ 21 ] demonstrated LODDS exhibited greater prognostic prediction accuracy in postoperative patients with Siewert type II AEG when compared to using PLN and LNR.…”
Section: Discussionmentioning
confidence: 99%
“…The only proven significant independent prognostic factor in the three cohorts was LODDS. LODDS is a newly identified promising index for prognosis prediction, which has been verified in several malignancies, such as small bowel adenocarcinoma [ 18 , 19 ], gastric cancer [ 20 ], and AEG [ 12 , 21 ]. With data from the SEER database, Xu et al [ 21 ] demonstrated LODDS exhibited greater prognostic prediction accuracy in postoperative patients with Siewert type II AEG when compared to using PLN and LNR.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, SBA is often diagnosed at more advanced stages compared to colorectal cancer ( 3 ). Additionally, SBA frequently presents with complications in the immediate area, including obstruction (40%) or bleeding (26%), further complicating its management ( 4 , 10 ). One study indicated that outcomes of SBAs appeared not to have improved with the progress of technology and time ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SBA frequently presents with complications in the immediate area, including obstruction (40%) or bleeding (26%), further complicating its management ( 4 , 10 ). One study indicated that outcomes of SBAs appeared not to have improved with the progress of technology and time ( 10 ). The explanation for this finding may be the lack of screening methods, resulting in missed opportunities for timely operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The TNMP stage was developed using a previously reported machine learning algorithm, an ensemble algorithm for clustering cancer data. [10][11][12][13][14] The main idea of ensemble methods is to use information from multiple models using multiple clustering algorithms to improve predictive performance in comparison to a single model. The performances of the TNM and TNMP models were assessed in terms of discriminatory ability (difference in survival between groups), monotonicity (increasing stage groups with decreasing patient survival), and homogeneity (difference in survival among patients within the same group), using multiple methods, including R 2 , linear trend χ 2 test, Cochran Armitage test for trends, Akaike information criterion, C-index, and integrated area under the curve.…”
Section: Development and Performance Assessment Of The Tnmp Stagementioning
confidence: 99%